The precise regulation of different COR genes by individual CBF transcription factors in Arabidopsis thaliana. Issue 2 (February 2017) - Shi, Yihao; Huang, Jiaying; Sun, Tianshu; Wang, Xuefei; Zhu, Chenqi; Ai, Yuxi; Gu, Hongya
Abstract: The transcription factors CBF1/2/3 are reported to play a dominant role in the cold responsive network of Arabidopsis by directly regulating the expression levels of cold responsive ( COR ) genes. In this study, we obtained CRISPR/Cas9‐mediated loss‐of‐function mutants of cbf1∼3 . Over 3, 000 COR genes identified by RNA‐seq analysis showed a slight but significant change in their expression levels in the mutants compared to the wild‐type plants after being treated at 4 °C for 12 h. The C‐repeat (CRT) motif (5′‐CCGAC‐3′) was enriched in promoters of genes that were up‐regulated by CBF2 and CBF3 but not in promoters of genes up‐regulated by CBF1. These data suggest that CBF2 and CBF3 play a more important role in directing the cold response by regulating different sets of downstream COR genes. More than 2/3 of COR genes were co‐regulated by two or three CBFs and were involved mainly in cellular signal transduction and metabolic processes; less than 1/3 of the genes were regulated by one CBF, and those genes up‐regulated were enriched in cold‐related abiotic stress responses. Our results indicate that CBFs play an important role in the trade‐off between cold tolerance and plant growth through the precise regulation of COR genes in the complicated transcriptional network. Abstract : The CBF‐dependent pathway is a plant‐specific response to low temperature. We obtained three single mutants in Arabidopsis thaliana lacking CBF1̃3 respectively using CRISPR/Cas9 technology. The RNA‐seq data indicated that each CBF regulated a different set of COR genes, which formed a complicated network in response to cold stress.